The Predictive Power of Self-Control for Life Outcomes - Deborah A. Cobb-Clark; Sarah C. Dahmann; Daniel A. Kamhöfer; Hannah Schildberg-Hörisch (Institute of Labor Economics (IZA), 2021)
This study investigates the predictive power of self-control for individuals and their children using population representative data. We use the well-established Brief Self-Control Scale to demonstrate that people's trait self-control is highly predictive of their life outcomes. Higher self-control is associated with better health, education, and employment outcomes as well as greater financial and overall well-being. Importantly, self-control often adds explanatory power beyond more frequently studied personality traits and economic preferences. The self-control of children is correlated with that of their parents, while higher parental self-control is also linked to fewer behavioral problems among children. Our results suggest that social interventions targeting self-control may be beneficial.
Keywords: D91; D01; J24; 330; Brief Self-Control Scale; personality traits; intergenerational transmission